Analisis Saluran Pemasaran Buah Naga Organik di Desa Jambewangi, Kabupaten Banyuwangi - Riza Rahimi Bachtiar; Abdul Holik; Danang SWPJ Widakdo (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2021)
Red dragon fruit is one of the strategic horticultural commodities that is growing rapidly in Banyuwangi because it has an exotic appearance and produces fruit that can be consumed. One area that cultivates organic red dragon fruit was Jambewangi. There were several problems in Jambewangi, such as farmers didn’t know profit distribution and cost’s share between marketing channels in organic red dragon fruit. The purpose of this study was to analyze the profit share and cost-share in Jambewangi. Determination of the research location used the purposive method and the method of determining the respondents used the snowball sampling method. The data used in this study are primary data and secondary data. The analysis used is the quantitative analysis used to measure the profit’s share and cost’s share. The results of the analysis can be concluded that the highest profit share value was found in channel 1 with 76.17% and the lowest cost share was also found in channel 1 with 23.83%. This result showed that channel 1 was the most efficient organic red dragon fruit marketing channel, compared to other marketing channels.